2019
DOI: 10.15587/1729-4061.2019.155738
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the carbonate ion on characteristics of electrochemically synthesized layered (α+β) nickel hydroxide

Abstract: Гiдроксид нiкелю широко використовується як активна речовина суперконденсаторiв. Найбiльш активними є зразки Ni(OH) 2 (α+β) шарової структури, синтезованi в щiлинному дiафрагмовому електролiзерi (ЩДЕ). Вивчено вплив карбонат-анiона на структуру та електрохiмiчнi властивостi гiдроксиду нiкелю, шляхом синтезу зразкiв в щiлинному дiафрагмовому електролiзерi з використанням для роздiлення електродних просторiв дiафрагми та катiонообмiнної мембрани. Експериментально показано, що при використаннi дiафрагми в щiлинно… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 49 publications
(35 reference statements)
2
40
0
Order By: Relevance
“…Both sulfate and carbonate can play a role in the formation of the (α+β) layered structure Ni(OH) 2 . By using the anion-exchange membrane [48], it was found that carbonate ions play a key role in the formation of the unique layered (α+β) Ni(OH) 2 structure during SDE synthesis. Intercalation of additional ions can occur due to their inclusion into the initial matrix.…”
Section: гідроксид нікелю широко використовується як активна речовинаmentioning
confidence: 99%
See 1 more Smart Citation
“…Both sulfate and carbonate can play a role in the formation of the (α+β) layered structure Ni(OH) 2 . By using the anion-exchange membrane [48], it was found that carbonate ions play a key role in the formation of the unique layered (α+β) Ni(OH) 2 structure during SDE synthesis. Intercalation of additional ions can occur due to their inclusion into the initial matrix.…”
Section: гідроксид нікелю широко використовується як активна речовинаmentioning
confidence: 99%
“…During crystallization, additional ions can stabilize the metastable α-form. However, the synthesis of the layered (α+β) structure in the SDE [48] was conducted at low carbonate concentrations in the anolyte.…”
Section: гідроксид нікелю широко використовується як активна речовинаmentioning
confidence: 99%
“…However, the intercalated anions often have specific functionality. For instance, stabilizing [28] or activating [29,30] anions are introduced to the LDH structure. LDH are promising materials to be used as nanocontainers for special anions, such as drugs [31,32], inhibitors [24], anionic dyes [33], sensor anions [34], etc.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…That is, either a bi-phase or layered (α+β) structure is formed. Thus, chemical synthesis in the presence of acetate ion results in the formation of the structure similar to electrochemically prepared Ni(OH) 2 in SDE [42,46]. In both cases, the stage of formation of the initial amorphous particle is slowed down.…”
Section: Discussion On the Results Of The Influence Of Acetate Anionsmentioning
confidence: 98%
“…So, this form is widely used in alkaline batteries [39] and hybrid supercapacitors [40]. β-Ni(OH) 2 can be precipitated chemically at low supersaturation or electrochemically in the slit-diaphragm electrolyzer [41,42]. High-temperature synthesis [43] and ammine complex decomposition [39] are also used.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%